Os Limites da BNCC para o Ensino de Ciências a partir da experiência da práxis autêntica freireana. - Simon, Gimena Andressa Venturini (Universidade Federal de São Carlos, 2023)
Science teaching has a history of approaches that, influenced by Brazilian pedagogical trends, differ in their curricular conceptions, many of which are traditional and banking, which end up distancing, relativizing and dichotomizing students' scientific knowledge. And opposition to progressive practices whose principle is based on the subjects' worldview. The National Common Curricular Base - BNCC presents a proposal aligned with a liberal perspective, which suggests contents and strategies based on a pre-established cut of reality. With these perspectives, this research comes to question to what extent, the BNCC as a curricular proposal for science teaching, contemplates the concrete experiences of the students, including their contradictory world views and participation in the construction of an authentic praxis? We sought to synthesize connecting principles between Scientific and Technological Education, Curriculum and the Critical Freirean Perspective and Walter Benjamin's concept of Authentic Experience. As a methodological process, a qualitative and critical analysis of the discourse present in the BNCC document was carried out, in the area of ​​Science Teaching in the Final Years of Elementary School. As a results, it was noted that there is not, in fact, a refusal of the subjects' worldview, but there is a cut of reality that does not necessarily come from the subjects, since they are pre-defined in competences and structural abilities throughout of learning cycles and based on objects of knowledge that organize the pedagogical proposal, making the experience of knowledge construction not formative, but reproductive. It is impoverished in experience and authenticity.
Los límites de la BNCC para la Enseñanza de Ciencias desde la experiencia de la praxis auténtica freireana.
Keywords: Ensino de Ciências; BNCC; Paulo Freire; Walter Benjamin; Enseñanza de Ciencias; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO::CURRICULOS ESPECIFICOS PARA NIVEIS E TIPOS DE EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO